2020
DOI: 10.1108/jima-08-2020-0228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of category attitudes on the relationship between SERVQUAL and satisfaction in Islamic banks; the role of disruptive societal-level events

Abstract: Purpose The purpose of this study is to modify the service quality scale (SERVQUAL) for measuring the performance of Islamic banks after modifying and validating it to fit the Islamic banking context. Furthermore, it provides insights for the limitations good service delivery has on maintaining favorable provider’s satisfaction in Islamic banks under conditions when category attitudes have been disrupted and made salient by major disruptive events. Design/methodology/approach Focus groups (managers of Islami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Hypothesis 1 stated that responsiveness has a significant impact on customer satisfaction and was supported by the results (β = 0.342, p = .000) which supported the premise that suggested that the repeated contact and salespersons' expression of inclination to offer help to customers are pivotal in establishing a satisfied customer relationship (Crosby et al, 1990). It has also been argued that although high service quality is associated with customer satisfaction, it gets dulled by category attitudes in the financial sector due to disruptive events, however, a responsive attitude helps in bridging the discontent (Farrag et al, 2020). The results are also aligned with the proposition that the use of technology to offer consistent and timely responses to customers has enhanced customer satisfaction (Iberahim et al, 2016;Islam et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…Hypothesis 1 stated that responsiveness has a significant impact on customer satisfaction and was supported by the results (β = 0.342, p = .000) which supported the premise that suggested that the repeated contact and salespersons' expression of inclination to offer help to customers are pivotal in establishing a satisfied customer relationship (Crosby et al, 1990). It has also been argued that although high service quality is associated with customer satisfaction, it gets dulled by category attitudes in the financial sector due to disruptive events, however, a responsive attitude helps in bridging the discontent (Farrag et al, 2020). The results are also aligned with the proposition that the use of technology to offer consistent and timely responses to customers has enhanced customer satisfaction (Iberahim et al, 2016;Islam et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, they found obstacles and so-called blocking effects for potential customers of Islamic banks such as "the perception of risk, image, and weak marketing reach". Farrag et al (2022) investigate the influence of category attitudes on the relationship between the service quality scale (SERVQUAL) and satisfaction in Islamic banks and focus in particular on the role of disruptive societal-level events. For this purpose, they interviewed focus groups consisting of managers of Islamic banks and applied exploratory factor analysis and CFA to test the validity of the developed scales and questionnaires.…”
Section: Research Results: Surveyed Papersmentioning
confidence: 99%
“…Many issues have thus far been explored, such as the potential determinants of customers' satisfaction with Islamic banking (Alharthi et al, 2021); an assessment of the success of the launching of the new bank digital platform for SMEs (Jegerson & Ahmad, 2021); the role of social media in the internet banking transition during the COVID-19 pandemic (Naeem & Ozuem, 2021); the impact of community relationship management (CoRM), relationship marketing orientation (RMO), customer engagement (CE), and brand trust (BT) on brand loyalty (BL) in a commercial bank (Wongsansukcharoen, 2022); the interrelatedness of entrepreneurial marketing (EM) and bank performance (Hilal & Tantawy, 2022); the influence of category attitudes on the relationship between the service quality scale (SERVQUAL) and satisfaction in Islamic banks (Farrag et al, 2022); the factors that prevent consumers from becoming clients of Islamic banks (Nugraha et al, 2022); the impact of internal marketing practices on employees' job satisfaction (Almaslukh et al, 2022) and the main determinants impacting the digital banking service adoption during the COVID-19 pandemic (Ngo et al, 2023). Source: Author's work…”
Section: Discussionmentioning
confidence: 99%
“…Many issues have thus far been explored, such as the potential determinants of customers' satisfaction with Islamic banking (Alharthi et al, 2021); an assessment of the success of the launching of the new bank digital platform for SMEs (Jegerson & Ahmad, 2021); the role of social media in the internet banking transition during the COVID-19 pandemic (Naeem & Ozuem, 2021); the impact of community relationship management (CoRM), relationship marketing orientation (RMO), customer engagement (CE), and brand trust (BT) on brand loyalty (BL) in a commercial bank (Wongsansukcharoen, 2022); the interrelatedness of entrepreneurial marketing (EM) and bank performance (Hilal & Tantawy, 2022); the influence of category attitudes on the relationship between the service quality scale (SERVQUAL) and satisfaction in Islamic banks (Farrag et al, 2022); the factors that prevent consumers from becoming clients of Islamic banks (Nugraha et 113…”
Section: Discussionmentioning
confidence: 99%